Fundamentals of laser micromachining - Schaeffer, Ronald D. (Boca Raton, FL : CRC Press, 2012)
Due to their flexible and efficient capabilities, lasers are often used over more traditional machining technologies, such as mechanical drilling and chemical etching, in manufacturing a wide variety of products, from medical implants, gyroscopes, and drug delivery catheters to aircraft engines, printed circuit boards, and fuel cells. Fundamentals of Laser Micromachining explains how laser technology is applied to precision micromachining. The book combines background on physics, lasers, optics, and hardware with analysis of markets, materials, and applications. It gives sufficient theoretical background for readers to understand basic concepts while including a further reading appendix for those interested in more detailed theoretical discussions.
Includes bibliographical references and index.
Keywords: Lasers -- Industrial applications; Rapid prototyping; Three-dimensional printing; Solid freeform fabication